The beginning of negotiations undertaken by the Conference of the Episcopate of Poland with the authorities of the Polish People Republic on regulating the legal status of the Catholic Church in Poland - Stępień, Marek (Prawo Kanoniczne, 2024)
After the Second World War communists took over the power in Poland. The main purpose of the ruling party was introducing the principles of Marxist philosophy. In the center of ideological fight was the Roman Catholic Church perceived as serious obstacle or even threat in achieving their goals. In 1980 the Polish authorities again declared their will to normalize relations and to reactivate the Joint Commission of representatives of the government and the Conference of the Episcopate of Poland. After the resumption of the session, the work proceeded constructively. The Joint Commission of representatives of the Conference of the Episcopate of Poland and the government of the Polish People's Republic appointed working teams, including the Working Group for Legislation, whose work was positively assessed by members of the Joint Commission. During the first two years of the Working Group for Legislation operation, the content of the draft act on the relationship between the State and the Catholic Church in Poland was agreed.